2011
DOI: 10.2190/ns.20.4.h
|View full text |Cite
|
Sign up to set email alerts
|

Double Presence, Paid Work, and Domestic-Family Work

Abstract: Double presence, which is understood as the need to respond simultaneously to the demands of paid and domestic-family work, mostly affects women and may negatively affect their health. Our hypothesis is that double presence increases as a function of the demands of domestic-family work, but is also associated with management practices related to the availability of time for paid work, prolonged and atypical work schedules, and heightened demands. A cross-sectional study was conducted with a representative samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 8 publications
(14 reference statements)
1
13
0
5
Order By: Relevance
“…This scale was not in the Danish COPSOQ I but we developed a preliminary version included in the Spanish COPSOQ Istas21 with the name of Double presence being understood as reflecting the need to respond simultaneously to the demands of a paid job and domestic‐family work. In the workplace, it is also associated with labor management practices related to the availability of time for paid work, prolonged and atypical work schedules, and heightened demands [Moreno et al, ]. It should be noted that all the results obtained for this dimension is satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…This scale was not in the Danish COPSOQ I but we developed a preliminary version included in the Spanish COPSOQ Istas21 with the name of Double presence being understood as reflecting the need to respond simultaneously to the demands of a paid job and domestic‐family work. In the workplace, it is also associated with labor management practices related to the availability of time for paid work, prolonged and atypical work schedules, and heightened demands [Moreno et al, ]. It should be noted that all the results obtained for this dimension is satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…). The important gender‐related inequalities seen in 2005 [Moreno et al, ] are reproduced in 2010, such that the proportion of women highly exposed in 2010? Is much higher than that for men (60.6% compared with 43.8%, data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This increase could be related to the increase in Work Pace, dealt with later on in the discussion, and with an increase in the proportion of wage‐earners working long hours (which rose from 26% in 2005 to 41% in 2010). In an earlier study [Moreno et al, ] based on the 2005 survey of psychosocial risks, it was found that the increase in working hours seemed to imply a loss of control over work schedules and an increase in double presence.…”
Section: Discussionmentioning
confidence: 99%
“…Any study of musculoskeletal conditions at work needs to consider these other factors, particularly in relation to the biopsychosocial model of health , which can also contribute to this association and which were not measured in the paper. An example of this is the ‘double burden’, which is explained as the need to respond simultaneously to the demands of paid work outside home with raising children and unpaid domestic‐family work . The biopsychosocial model of health was first proposed by Engel in 1997 and applied to musculoskeletal pain by Waddell in 1987 .…”
mentioning
confidence: 99%